2009
DOI: 10.1007/s11010-009-0292-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of CYP3A genes, CYP2B22, and MDR1, MRP1, MRP2, LRP efflux transporters in brain of control and rifampicin-treated pigs

Abstract: The in vivo effect of rifampicin, a potent ligand of PXR, on gene expression of CYP2B22, 3A22, 3A29, 3A46, CAR, PXR and MDR1, MRP1, MRP2, LRP transporters in liver and cortex, cerebellum, midbrain, hippocampus, meninges and brain capillaries of pig was investigated. Animals were treated i.p. with four daily doses of rifampicin (40 mg/kg). The basal mRNA expressions of the individual CYP3As, CYP2B22, CAR, and PXR in various brain regions, except meninges, were about or below 10% of the corresponding hepatic mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The Kp value of rifampicin (0.03, Table 1) was much lower than that of caffeine (0.5, Table 1) indicating rifampicin poor brain permeability compared to caffeine, which could be related to differences in plasma protein binding of both drugs as rifampicin has higher protein binding (88%) [48] compared to caffeine (10–37%) [49, 50]. While it is difficult to correlate plasma or brain levels of both drugs to the degree of enhanced expression of either transport protein, rifampicin and caffeine may not need to cross the BBB to upregulate LRP1or P-gp [13].…”
Section: Discussionmentioning
confidence: 99%
“…The Kp value of rifampicin (0.03, Table 1) was much lower than that of caffeine (0.5, Table 1) indicating rifampicin poor brain permeability compared to caffeine, which could be related to differences in plasma protein binding of both drugs as rifampicin has higher protein binding (88%) [48] compared to caffeine (10–37%) [49, 50]. While it is difficult to correlate plasma or brain levels of both drugs to the degree of enhanced expression of either transport protein, rifampicin and caffeine may not need to cross the BBB to upregulate LRP1or P-gp [13].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, most studies have only reported the transcript expression of hPXR in brain cortex and cerebellum (Nishimura et al 2004;Miki et al 2005;Dauchy et al 2009). CAR mRNA expression has been observed in different regions of the human brain and in brain capillaries isolated from pigs and mice (Savkur et al 2003;Lamba et al 2004;Nishimura et al 2004;Dauchy et al 2008;Nannelli et al 2010). In our previous publication, hPXR protein expression was demonstrated in hCMEC/D3 cells, however the role of P-gp regulation was not investigated (Zastre et al 2009).…”
Section: (B)mentioning
confidence: 99%
“…In the brain, expression of PXR mRNA and protein have been detected in the cortex, brain capillaries and primary cultures of brain microvessel endothelial cells obtained from mice, rats and pigs (Bauer et al 2004(Bauer et al , 2006(Bauer et al , 2008Nishimura et al 2004;Narang et al 2008;Ott et al 2009;Nannelli et al 2010). In humans, most studies have only reported the transcript expression of hPXR in brain cortex and cerebellum (Nishimura et al 2004;Miki et al 2005;Dauchy et al 2009).…”
Section: (B)mentioning
confidence: 99%
“…2 | AN OVERVIEW OF NR1I2 (PXR) AND NR1I3 (CAR) NR1I2 and NR1I3 possess many structural features present in classic NRs, including the DNA-binding domain, an N-terminal AF-1 domain and a C-terminal LB ligand-binding domain D (Khorasanizadeh & Rastinejad, 2016;Mullican et al, 2013). NR1I2 and NR1I3 are 50-kDa proteins highly expressed in liver and intestine (Giessmann et al, 2004;Nannelli et al, 2010). Further studies have demonstrated that their expression pattern is more ubiquitous than initially thought, as other organs including brain, kidneys and heart also express both of these receptors (Lamba et al, 2004;Marini et al, 2007;Miki, Suzuki, Tazawa, Blumberg, & Sasano, 2005;Nannelli et al, 2010;Nishimura, Naito, & Yokoi, 2004;Savkur et al, 2003).…”
mentioning
confidence: 99%